To solve the equation \((x+4)(x-2)=0\), we can use the property that if a product of two factors is zero, at least one of the factors must be zero. We can set each factor equal to zero and solve for \(x\).
-
Set the first factor equal to zero: \[ x + 4 = 0 \] Subtracting 4 from both sides gives: \[ x = -4 \]
-
Set the second factor equal to zero: \[ x - 2 = 0 \] Adding 2 to both sides gives: \[ x = 2 \]
Now we have found two solutions:
\[ x = -4 \quad \text{and} \quad x = 2 \]
Therefore, the values of \(x\) that make the equation equal to zero are:
\[ \boxed{-4 \text{ and } 2} \]